2008
DOI: 10.1111/j.1365-2052.2008.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of the solute carrier gene family in chicken intestine from the late embryonic to early post‐hatch stages

Abstract: Intestinal development during late embryogenesis and early post-hatch has a long-term influence on digestive and absorptive capacity in chickens. The objective of this research was to obtain a global view of intestinal solute carrier (SLC) gene family member expression from late embryogenesis until 2 weeks post-hatch with a focus on SLC genes involved in uptake of sugars and amino acids. Small intestine samples from male chicks were collected on embryonic days 18 (E18) and 20 (E20), day of hatch and days 1, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…In the present study, PepT1 expression was greater in ES3 chicks than those from ES14 chicks from 480 h of incubation to the end of hatch window at 514 h. In addition, compared with ES14 chicks, ES3 chicks exhibited greater SGLT1 expression at the end of the hatch window. Enhanced villus surface area along with upregulated expression of nutrient transporters of ES3 chicks at the end of hatch window appears to positively contribute to the nutrient absorption and digestion as reported previously (Li et al, 2008). Our findings suggested that ES3 chicks would have a greater aptitude for absorption of proteins and carbohydrates when food intake begins compared with ES14 chicks.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, PepT1 expression was greater in ES3 chicks than those from ES14 chicks from 480 h of incubation to the end of hatch window at 514 h. In addition, compared with ES14 chicks, ES3 chicks exhibited greater SGLT1 expression at the end of the hatch window. Enhanced villus surface area along with upregulated expression of nutrient transporters of ES3 chicks at the end of hatch window appears to positively contribute to the nutrient absorption and digestion as reported previously (Li et al, 2008). Our findings suggested that ES3 chicks would have a greater aptitude for absorption of proteins and carbohydrates when food intake begins compared with ES14 chicks.…”
Section: Discussionsupporting
confidence: 80%
“…Expressions of PepT1 and SGLT1 influence the development of intestinal digestive and absorptive functions. As intestinal development during embryogenesis has a long-term influence on digestive and absorptive capacity in chickens, previous studies in chicks have concentrated on the presence of PepT1 and SGLT1 during embryonic growth Li et al, 2008;Speier et al, 2012;Miska et al, 2014). Their upregulation between 18 days of incubation and 14 days post-hatch indicates the importance of those transporters for post-hatch growth and optimum development (Gilbert et al, 2007;Li et al, 2008;Mott et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, additional studies are needed to identify the exact mechanisms that regulate the expression of these gene products during development, and whether alterations in mRNA stability, post-transcription or translation are also involved in this ontogenic regulation of folate transport in the intestine. The ontogenic downregulation of Slc19a1 expression was in agreement with the findings of Li et al (2008) who reported that intestinal Slc19a1 mRNA abundance at D14 post-hatch was lower than that at DOH in broiler chickens analyzed by DNA microarrays, however data regarding PCFT was not presented. Taken together, the available evidence from both avian and mammalian species support the existence of mechanisms to prepare the developing animal for folate uptake post-hatch or post-natally.…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, our understanding of AA and peptide transport across the intestinal epithelia of chickens is not well understood, and some of the transport systems and their regulation in the gastrointestinal tract of chickens (G. gallus domesticus) was only recently uncovered (Chen et al., Gilbert et al, 2008;Li et al, 2008). However, there is still a great need for better understanding of avian peptide and AA absorptive mechanisms, particularly during practical circumstances, of which the study herein investigates.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these transport systems have been recently recognized in the enterocytes of chickens (Chen et al, 2005;Gilbert et al, 2007;Gilbert et al, 2008;Li et al, 2008). Gilbert et al (2008) AT, CAT2, y + LAT2, and EAAT3 as those showing a differential expression in intestinal mRNA abundance in chickens in response to diet type.…”
Section: Dietary Protein Effects On Growth Performance Carcass Traitmentioning
confidence: 99%